The role of geography in developing the educational reality in Iraq - Al-Shammari, hussein Rahim Hasoon; Ali Hadi, khloud (Al-Adab Journal, 2019)
Geographical studies, especially human beings, have often contributed to diagnosing the problems faced by societies, especially after population growth and the expansion of urban development, and some peoples have tried to use some geographical experiences and research to develop and develop their services in a sustainable manner, and among the most important services The services that are often used by these societies, especially the highly developed ones, are the services that are concerned with the educational reality (educational services) that fall within the geography of cities, which is one of the branches of human geography as it has become an urgent necessity, but its development and attention to it has become the progress and development of peoples, and that in The way to achieve development goals on the one hand, and to protect the environment with the educational services it contains and the problems and obstacles it contains on the other hand. Geographical scientific efforts have been concerted in identifying these problems and trying to diagnose them and ways to address them with the available mechanisms in order to develop them and increase their efficiency from the relevant authorities. We will address in this research the role of geography and the geographic researcher and the studies presented in order to improve the educational reality in Iraq in order to address one of the contemporary Iraqi problems so that we can diagnose the role of geography in the development of Iraqi society, as this research included three axes, the first axis came to deal with the concept of science Geography and its relationship to development. As for the second axis, we dealt with the relationship between geography and education, while the third axis came to stand on the future prospects for the development of education in Iraq, and the research was concluded with results and proposals.